SHOPPING TOURISM IS A MANIFESTATION OF THE COMMERCIAL DYNAMICS IN THE ALGERIAN CITY – A CASE STUDY: SOUK AHRAS CITY - Tourghi Hani; Testas Mohamed; Sid Ahmed Soufiane (International Journal of Innovative Technologies in Social Science, 2023)
The aim of this research is to study the reality of shopping tourism and its impact on the growth, organization, and dynamics in an Algerian city: Souk Ahras city as a case study. It highlights the various forms and aspects of shopping tourism and its influence on the commercial, economic, social, and cultural sectors. The research also examines the strengths, weaknesses, opportunities, and threats associated with shopping tourism in the city of Souk Ahras, and formulates the general strategy for the city using SWOT analysis. The results derived from the strategy and field investigation indicate that shopping tourism in the city of Souk Ahras is influenced by several factors. These factors include the commercial weight of the city, its strategic geographic location, its openness to the border area, and the significant influx of tourists, especially from Tunisia. The city has experienced substantial commercial development through markets and shopping centers, contributing to increased inputs and resources. The availability of goods and products at competitive prices can be attributed to the social support policy on raw materials in Algeria. Additionally, the growth of the informal sector has provided a wide variety of products. All of these factors have positioned the city of Souk Ahras as an attraction for tourist flows, making shopping tourism a significant urban phenomenon that influences the organization and economy of the city.